Production Management of Regional Language Broadcast Program 'Nusantara Kini Malam' at Jawa Pos Multimedia TV Jakarta - Lingga, M Lingga Aryo Maeza Hafiz; Krisna Mulawarman (Jogjakarta Communication Conference (JCC), 2024)
The regional language broadcast program "Nusantara Kini Malam" covers events from all over Indonesia and is organized by the Jawa Pos local television network, especially focusing on major national news. This program features various stories from different corners of the archipelago and highlights aspects rarely shown by other television stations. Within the program, there is a "Satu Nusa" segment, which presents news in regional languages. "Nusantara Kini Malam" is scheduled to be broadcast daily at 19:00 and is repeated on all television channels connected to Jawa Pos Multimedia. This research aims to evaluate the production management of the regional language broadcast program "Nusantara Kini Malam" at Jawapos Multimedia TV Jakarta for future improvements using POAC management theory, which stands for Planning, Organizing, Actuating, and Controlling. This study employs a qualitative method with a case study approach, utilizing interview, observation, and documentation techniques. The results indicate that evaluating the production management of the "Nusantara Kini Malam" program can enhance performance, optimize resource use, and improve the quality of regional language content, thereby increasing viewer satisfaction and ultimately helping the television station gain a competitive advantage in the regional language broadcasting market.